How to do just about anything : 1001 practical skills and lifestyle solutions - Bastable, Jonathan; Binney, Ruth; Shepherd, Rose (New South Wales : Reader's Digest, 2012)
Want to know how to say'thank you' in 12 languages? Or how to dance the samba? Or make a sponge cake? Are you having trouble removing rust from your lawn-mower blades? Are you anxious to know how to protect yourself against identity theft? This indispensable A-Z guide is packed with simple solutions to all those tricky problems life can throw at you. And, it's full of skills old and new, fun and functional to ensure that you'll never be at a loss or a loose end again. Whether your aim is to keep a lid on your energy bills or learn how to play tiddlywinks, you'll find out how right here, quickly and easily.
Keywords: Home economics -- Handbooks, manuals, etc; Life skills -- Handbooks, manuals, etc; Dwellings -- Maintenance and repair -- Handbooks, manuals, etc; Problem solving -- Handbooks, manuals, etc